AKAL, WAHYU, DAN KASB MANUSIA MENURUT JABARIYAH DAN QADARIYAH - Edi Sumanto (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2016)
Abstract: Reason,  Revelation,  And Human  Efforts According to  Jabarites And Qadarites. This  article describes the  views  of Qadarites and  Jabarites about  the  revelation,  reason, and  human efforts.  The method used  is based on  a  literature   library  from  books,  magazines and  articles  related. The  study concluded: first, for Jabarites, reasoning has no meaning, because reasoning is of no use to humans, they are  more  dominant subject to revelation or the  provision  of God in their every activities,  so human just only accept anything  that has  been given by The Creator.  While according to Qadarites, Reasoning is to proportionate the provisions  that God has  made for man,  to contribute to the act of doing, good  or bad. In connection with the concept of revelation,  for Jabarites that the revelation is a source of important and basic to those  that must be followed,  because the verses they are using is a verse to support  the argument they  use.  While  revelation in according to  Qadarites is considered as  to  proportionate their  opinion, because God disposes all human actions,  but humans have a stake in it in order to try and select  it.Finally, in Human  efforts, for Jabarites that no efforts, because everything  he does  has been determined by God. There  is no human power  to do in doing something. however, according to Qadarites that human effort is depend on human beings  themselves and the result depends according what  he has done  without  any intervention from God.